2020
DOI: 10.21608/nrmj.2020.73438
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxins and aflatoxigenic fungal contamination of common poultry feed products in Katsina State, Nigeria

Abstract: This study was conducted to screen the common poultry feed products sold within Katsina State, Nigeria, for the presence of aflatoxigenic fungi and aflatoxins. A total of 15 poultry feed samples from 3 major producing companies were purchased from retailers, and then cultured for fungal isolation on potato dextrose agar (PDA) supplemented with Cycloheximide. Fungal colonies were identified using standard mycological techniques. The samples were further extracted using a methanol-water solvent (v/v) 1:2, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…However, as only a few studies are reporting consumer-level fungal contamination of chicken feed in Malaysia and Nigeria, it is clear that our research findings offer insight into the underlying mycoflora contamination of these items. The average contamination level across all sample categories was higher than the ICMSF's acceptable range of 2.0 to 5.0 log CFU/g (ICMSF, 2006) and it is consistent with other studies that document excessive fungal contamination in poultry feeds and food grains from Malaysia (Samsudin and Abdullah, 2013;Zulkifli and Zakaria, 2017;Norlia et al, 2018;Yazid et al, 2021) and Nigeria (Ezekiel et al, 2014;Monday et al, 2014;Egbuta et al, 2015;Ibrahim et al, 2018;Okafor and Eni, 2018;Salisu and Almajir, 2020;. On the contrary, Roslan (2016) reported lower fungal bioburden in Malaysian poultry feeds and grain-based foods, respectively.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…However, as only a few studies are reporting consumer-level fungal contamination of chicken feed in Malaysia and Nigeria, it is clear that our research findings offer insight into the underlying mycoflora contamination of these items. The average contamination level across all sample categories was higher than the ICMSF's acceptable range of 2.0 to 5.0 log CFU/g (ICMSF, 2006) and it is consistent with other studies that document excessive fungal contamination in poultry feeds and food grains from Malaysia (Samsudin and Abdullah, 2013;Zulkifli and Zakaria, 2017;Norlia et al, 2018;Yazid et al, 2021) and Nigeria (Ezekiel et al, 2014;Monday et al, 2014;Egbuta et al, 2015;Ibrahim et al, 2018;Okafor and Eni, 2018;Salisu and Almajir, 2020;. On the contrary, Roslan (2016) reported lower fungal bioburden in Malaysian poultry feeds and grain-based foods, respectively.…”
Section: Discussionsupporting
confidence: 86%
“…In general, the high bioburden of fungi obtained in the present study may be due to long-time storage and poor storage conditions used by the poultry feed sellers, as opined by Habib et al (2015), Ibrahim et al (2018) and Salisu and Almajir (2020) who observed that majority of the Nigerian poultry sellers use insufficient and poor storage facilities (locked-up stores without air conditioning system or good ventilation). As a result, livestock feeds are frequently contaminated with mycotoxins and fungi in Nigeria.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Aflatoxins are a group of low molecular weight toxic proteins compounds produced as secondary metabolites by fungi of the genera Aspergillus. Specie of A. flavus that grow under favourable conditions are excellent source of Aflatoxins (Salisu and Almajir, 2020). Several fungi were known to contaminate foods/feeds and consequently produce wide array of toxic metabolites and mycotoxins (Oliveira et al, 2017;Reddy et al, 2010;Uhlig et al, 2013;(Zaki, Shaheen and Rizzi, 2012;Berthiller et al, 2013;Alshannaq and Yu, 2017).…”
Section: Introductionmentioning
confidence: 99%